THE EFFECT OF TRADING DAYS AND SYSTEMATIC RISK ON STOCK RETURN VOLATILITY: STUDY OF LQ-45 COMPANIES ON THE INDONESIAN STOCK EXCHANGE DURING THE COVID-19 PANDEMIC - Hendayana, Yana; Putra, Ivan Gumilar Sambas; Hertina, Dede (Media Riset Akuntansi, Auditing & Informasi, 2025)
This research aims to determine the effect of trading days and systematic risk on stock return volatility. This study is based on the phenomenon of trading day anomalies that often influence market movements, as well as the importance of understanding systematic risk in investment decision-making. This research is quantitative research with a causal design and uses multiple linear regression analysis. The research object is stocks included in the LQ-45 index. The research findings indicate that trading days and systematic risk have a significant effect on stock return volatility. These findings reinforce the growing literature on trading day anomalies and stock return volatility, and provide empirical evidence of the factors that influence stock volatility in different economic and market dynamics. The practical implications of this research suggest the need for risk management strategies tailored to volatile market conditions, as well as the consideration of using derivative financial instruments, portfolio diversification to protect stock value, and enhancing resilience against market fluctuations.